Recurrence Risk Perception and Quality of Life Following Treatment of Breast Cancer - Hawley, Sarah T. (Breast Cancer Res Treat, 2016)
PURPOSE: Little is known about different ways of assessing risk of distant recurrence following cancer treatment (e.g., numeric or descriptive). We sought to evaluate the association between overestimation of risk of distant recurrence of breast cancer and key patient reported outcomes, including quality of life and worry. METHODS: We surveyed a weighted random sample of newly diagnosed patients with early-stage breast cancer identified through SEER registries of Los Angeles & Georgia (2013-14) ∼2 months after surgery (N=2578, RR=71%). Actual 10-year risk of distant recurrence after treatment was based on clinical factors for women with DCIS & low risk invasive cancer (Stg 1A, ER+HER2-, Gr 1-2). Women reported perceptions of their risk numerically (0 – 100%), with values ≥10% for DCIS & ≥20% for invasive considered overestimates. Perceptions of “moderate, high or very high” risk were considered descriptive overestimates. In our analytic sample (N=927), we assessed factors correlated with both types of overestimation and report multivariable associations between overestimation and QoL (PROMIS physical & mental health) and frequent worry. RESULTS: 30.4% of women substantially overestimated their risk of distant recurrence numerically and 14.7% descriptively. Few factors other than family history were significantly associated with either type of overestimation. Both types of overestimation were significantly associated with frequent worry, and lower QoL. CONCLUSIONS: Ensuring understanding of systemic recurrence risk, particularly among patients with favorable prognosis, is important. Better risk communication by clinicians may translate to better risk comprehension among patients and to improvements in QoL.